The effectiveness of traditional probiotic food. Overview of scientific reports on the quality of probiotics in fermented foods and the health benefits of their consumption - Martyna Kępczyk; Mikołaj Tokarski; Jakub Misiak; Michał Urbaś; Dawid Kościołek; Aleksandra Kościołek; Kaja Surowiecka; Miłosz Ojdana; Konrad Szalbot; Konrad Czchowski (Kazimierz Wielki University, 2024)
Introduction and purpose The term "probiotic" rooted in Latin, signifies 'for life,' reflecting the historical use of fermented products for therapeutic purposes. While browsing many websites devoted to healthy eating or popular science topics, we often came across the topic of probiotic food without any confirmation by scientific research. The aim of this paper is to confirm or exclude the presence of probiotics in popular foods. State of knowledge The paper reviews  literature on the health benefits of various food that is traditionally considered probiotic, focusing on how they impact on varied health conditions. Defined by the WHO as living microorganisms conferring health benefits when consumed adequately, probiotics, mainly bacteria from Lactobacillus and Bifidobacterium genera, play a vital role in maintaining gut microbiota balance, regulating digestion, supporting the immune system and influencing mental and cardiovascular health. In addition, the paper also  searches for scientific basis for their action. Material and methods A review of the literature available in the "PubMed" and Google Schoolar was conducted. We focused on checking whether the microorganisms contained in pickled food meet the WHO criteria for probiotics. Summary Our review managed to prove the probiotic effect of almost all presented food, except for miso. By reviewing many articles, we shed a lot of uncertainty on the repeated myth about the lack of probiotic effect of cucumbers preserved in vinegar  and what is more, we found scientific assumptions about the probiotic effect of vinegar itself. Fermented food contains numerous strains of bacteria that are resistant to acid, bile and temperature in the human digestive tract and can be effectively used as a source of probiotics. Additionally, compared to probiotics from the pharmacy, fermented products provide not only probiotics, but also nutritional value, valuable fiber and vitamins, benefiting to our health.